Model Predictive Speed Control of Axial Piston Motors*. Issue 18 (2016) - Zeman, P.; Kemmetmüller, W.; Kugi, A.
Abstract: The efficiency of conventional mechanical drive concepts can be increased by utilizing hydraulic components. Despite the comparatively low efficiency of hydraulic systems, the efficiency of the overall system is increased by converting kinetic energy into energy stored in a hydraulic accumulator. Furthermore, a hydrostatic transmission achieves a decoupling of the drive speeds and thus allows to operate the prime mover in a set point with increased efficiency. The advantages of such hybrid hydraulic drives are evident in the field of mobile applications with a large amount of stop-and-go cycles. Variable displacement axial piston pumps/motors typically connect the mechanical and the hydraulic subsystems by simultaneously providing a high-dynamic torque behavior. The present contribution aims at applying model predictive control (MPC) to the speed control of an axial piston motor in a hybrid hydraulic drive. Compared to classical controller strategies, the input constraints of the system are systematically accounted for in the controller design. The feasibility of the control algorithm is demonstrated on an industrial test bench of the axial piston motor.